α-Chaconine Facilitates Chondrocyte Pyroptosis and Nerve Ingrowth to Aggravate Osteoarthritis Progression by Activating NF-κB Signaling - Zhang Z; Fu F; Bian Y; Zhang H; Yao S; Zhou C; Ge Y; Luo H; Chen Y; Ji W; Tian K; Yue M; et al. (Dove Medical Press, 2022)
Zhiguo Zhang,1,2,* Fangda Fu,1,2,* Yishan Bian,1,2,* Huihao Zhang,1,2 Sai Yao,1,2 Chengcong Zhou,1,2 Yuying Ge,2 Huan Luo,3 Yuying Chen,4 Weifeng Ji,1 Kun Tian,1 Ming Yue,5 Weibin Du,6 Hongting Jin,1 Peijian Tong,1 Chengliang Wu,1,2 Hongfeng Ruan1,2 1Institute of Orthopaedics and Traumatology, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Traditional Chinese Medicine), Hangzhou, People's Republic of China; 2The First Clinical Medical College of Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 3Department of Pharmacy, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, People's Republic of China; 4The Fourth Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 5Department of Physiology, College of Basic Medical Sciences, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 6Research Institute of Orthopedics, The Affiliated Jiangnan Hospital of Zhejiang Chinese Medical University, Hangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Hongfeng Ruan; Chengliang Wu, Institute of Orthopaedics and Traumatology, The First Affiliated Hospital of Zhejiang Chinese Medical University, 548 Binwen Road, Hangzhou, 310053, People's Republic of China, Fax +86 571 86613684, Email rhf@zcmu.edu.cn; wcl@zcmu.edu.cnBackground: With the rapid growth of the elderly population, the incidence of osteoarthritis (OA) increases annually, which has attracted extensive attention in public health. The roles of dietary intake in controlling joint disorders are perhaps one of the most frequently posed questions by OA patients, while the information about the interaction between dietary intake and OA based on scientific research is limited. α-Chaconine is the richest glycoalkaloid in eggplants such as potatoes. Previous evidence suggests that α-Chaconine is a toxic compound to nervous and digestive systems with potentially severe and fatal consequences for humans and farm animals, but its effect on OA development remains obscure.Objective: To determine whether α-Chaconine deteriorates OA progression through sensory innervation and chondrocyte pyroptosis via regulating nuclear factor-κB (NF-κB) signaling, providing evidence for a possible linkage between α-Chaconine and OA progression.Methods: We established a mouse OA model by destabilization of medial meniscus (DMM) surgery and then intra-articular injection of 20 or 100 μM α-Chaconine into the OA mice for 8 and 12 weeks. The severity of OA progression was evaluated by histological staining and radiographic analyses. The expressions of matrix metabolic indicators, Col2, Mmp3, and Mmp13, as well as pyroptosis-related proteins, Nlrp3, Caspase-1, Gsdmd, IL-1β, IL-18, were determined by immunohistochemistry. And the changes in sensory nerve ingrowth and activity of NF-κB signaling were determined by immunofluorescence.Results: We found that α-Chaconine could exacerbate mouse OA progression, resulting in subchondral sclerosis, osteophyte formation, and higher OARSI scores. Specifically, α-Chaconine could augment cartilage matrix degradation and induce chondrocyte pyroptosis and nerve ingrowth. Mechanistical analysis revealed that α-Chaconine stimulated NF-κB signaling by promoting I-κB α phosphorylation and p65 nuclear translocation.Conclusion: Collectively, our findings raise the possibility that α-Chaconine intake can boost chondrocyte pyroptosis and nerve ingrowth to potentiate OA progression by activating NF-κB signaling.Graphical Abstract: Keywords: α-Chaconine, osteoarthritis, pyroptosis, nerve ingrowth, NF-κB signaling